﻿Mycobiont-specific primers facilitate the amplification of mitochondrial small subunit ribosomal DNA: a focus on the lichenized fungal genus Melanelia (Ascomycota, Parmeliaceae) in Iceland - Maonian Xu; Yingkui Liu; Erik Möller; Scott LaGreca; Patricia Moya; Xinyu Wang; Einar Timdal; Hugo de Boer; Eva Barreno; Lisong Wang; Holger Thüs; Ólafur Andrésson; et al. (MycoKeys, 2023)
The fungal mitochondrial small subunit (mtSSU) ribosomal DNA is one of the most commonly used loci for phylogenetic analysis of lichen-forming fungi, but their primer specificity to mycobionts has not been evaluated. The current study aimed to design mycobiont-specific mtSSU primers and highlights their utility with an example from the saxicolous lichen-forming fungal genus Melanelia Essl. in Iceland. The study found a 12.5% success rate (3 out of 24 specimens with good-quality mycobiont mtSSU sequences) using universal primers (i.e. mrSSU1 and mrSSU3R), not including off-target amplification of environmental fungi, e.g. Cladophialophora carrionii and Lichenothelia convexa. New mycobiont-specific primers (mt-SSU-581-5’ and mt-SSU-1345-3’) were designed by targeting mycobiont-specific nucleotide sites in comparison with environmental fungal sequences, and assessed for mycobiont primer specificity using in silico PCR. The new mycobiont-specific mtSSU primers had a success rate of 91.7% (22 out of 24 specimens with good-quality mycobiont mtSSU sequences) on the studied Melanelia specimens. Additional testing confirmed the specificity and yielded amplicons from 79 specimens of other Parmeliaceae mycobiont lineages. This study highlights the effectiveness of designing mycobiont-specific primers for studies on lichen identification, barcoding and phylogenetics.